Expression profiling of metabolic genes in response to methyl jasmonate reveals regulation of genes of primary and secondary sulfur-related pathways in Arabidopsis thaliana - Jost, Ricarda; Bogs, Jochen; Wachter, Andreas; Wirtz, Markus; Rausch, Thomas; Hell, Rüdiger (Photosynthesis research, 2005)
The treatment of Arabidopsis thaliana with methyl jasmonate was used to investigate the reaction of 2467 selected genes of primary and secondary metabolism by macroarray hybridization. Hierarchical cluster analysis allowed distinctions to be made between diurnally and methyl jasmonate regulated genes in a time course from 30 min to 24 h. 97 and 64 genes were identified that were up- or down-regulated more than 2-fold by methyl jasmonate, respectively. These genes belong to 18 functional categories of which sulfur-related genes were by far strongest affected. Gene expression and metabolite patterns of sulfur metabolism were analysed in detail, since numerous defense compounds contain oxidized or reduced sulfur. Genes encoding key reactions of sulfate reduction as well as of cysteine, methionine and glutathione synthesis were rapidly up-regulated, but none of the known sulfur-deficiency induced sulfate transporter genes. In addition, increased expression of genes of sulfur-rich defense proteins and of enzymes involved in glucosinolate metabolism was observed. In contrast, profiling of primary and secondary sulfur metabolites revealed only an increase in the indole glucosinolate glucobrassicin upon methyl jasmonate treatment. The observed rapid mRNA changes were thus regulated by a signal independent of the known sulfur deficiency response. These results document for the first time how comprehensively the regulation of sulfur-related genes and plant defense are connected. This interaction is discussed as a new approach to differentiate between supply- and demand-driven regulation of the sulfate assimilation pathway.
Gesehen am 17.05.2017